2008
DOI: 10.1016/j.jpcs.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of on the growth and thermal properties of K2SO4 crystal

Abstract: Single crystals of pure and Cd 2þ -doped potassium sulfate were grown from aqueous solutions by the slow evaporation technique. From nutrient solutions with a CdSO 4 concentration of 4 wt% crystals containing 0.014 wt% dopant concentration could be obtained. The X-ray diffraction patterns of powdered crystals confirmed their crystal structures for both cases. Thermal analysis of pure crystals shows that the a-b phase transformation peak around 580 1C is superimposed with spurious effects, while for Cd 2þ -dope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…[ 22 ] also explained the concentration and supersaturation effects on the impurity action of traces Fe (III) by using a proposed model, and found that the impurity effectiveness factor increased inversely proportional to the supersaturation as predicted by the model. Others studied the primary nucleation process and crystal growth process of K 2 SO 4 solutions in the presence of ionic impurities, [ 23,24 ] such as Cd 2+ , Sr 2+ , Ba 2+ , Ag + , Pb 2+ , and Ni 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] also explained the concentration and supersaturation effects on the impurity action of traces Fe (III) by using a proposed model, and found that the impurity effectiveness factor increased inversely proportional to the supersaturation as predicted by the model. Others studied the primary nucleation process and crystal growth process of K 2 SO 4 solutions in the presence of ionic impurities, [ 23,24 ] such as Cd 2+ , Sr 2+ , Ba 2+ , Ag + , Pb 2+ , and Ni 2+ .…”
Section: Introductionmentioning
confidence: 99%